Factors Affecting Students’ Acceptance of Learning Simulation Tools in Computing Education Courses from Social, Technology, and Personal Trait Perspectives - Dri Handarkho, Yonathan; Devi Indriasari, Theresia; Sigit Purnomo , Yohanes; Kartika Sari Dewi, Findra; Yayu' Palangan, Citra; Citrayasa, Vinindita; Gonzaga Pradnya, Aloysius; Herlina (Journal of Information and Organizational Sciences, 2025)
This study presents a theoretical model to explore the factors influencing students' acceptance of simulation tools in computing education. These factors include social influences, technology-related aspects, and personal characteristics. The term "simulation tools" refers to systems that can replicate complex processes and situations, providing students with realistic, hands-on experiences without the risks or costs associated with physical setups. To validate the proposed model, 312 responses from university students were collected. A cross-sectional online survey was conducted, and the participants were selected through purposive sampling. The findings indicated that subjective norms have the most significant direct effect on students' perceptions of usefulness, influencing their views on learning outcomes from using simulation tools in computing education courses. Additionally, social support and self-efficacy were also found to have significant effects. However, the impacts of fidelity and innovativeness were not supported. This study sets itself apart from previous research by using a comprehensive approach to explore the factors influencing student acceptance of simulation tools in computing education. Specifically, this research develops a theory based on the Technology Acceptance Model (TAM) and expands it by incorporating environmental factors and personal characteristics of students.